Changing the Position of Transnational Corporations in the Global Economy – Implications for International Financial Markets - Rosińska-Bukowska, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article shows changing the position of transnational corporations (TNCs) in the global economy. The article make an attempt to assess the impact of the increasing role of TNCs in the global flows of capital and the consequences of this fact for the international financial markets. The article consists of three parts. The first part – the evolution of transnational corporations as a basis for obtaining a strong position in the global economy. The second part – the analysis of the potential of the most powerful transnational corporations against the background of GDP of countries and the global capital market value. The third part – an attempt to assess the impact of corporations on international capital flows and functioning of financial markets.